Renormalizing an infinite rational IET - Hooper, W. Patrick; Rafi, Kasra; Randecker, Anja (Discrete and continuous dynamical systems, 2020)
We study an interval exchange transformation of [0; 1] formed by cutting the interval at the points 1 n and reversing the order of the intervals. We find that the transformation is periodic away from a Cantor set of Hausdorff dimension zero. On the Cantor set, the dynamics are nearly conjugate to the 2-adic odometer.
Gesehen am 09.06.2021